2014
DOI: 10.4149/neo_2014_014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Expression of CES2, UGT1A1, and GUSB in colorectal cancer tissues and aberrant methylation

Abstract: Irinotecan (CPT-11) is considered an important drug in the treatment of colorectal cancer, but its continuous administration reduces its sensitivity and influences the curative effect. The metabolism of CPT-11 is mainly controlled by carboxy-lesterase (CES), UDP-glucuronosyltransferase 1A (UGT1A), and β-glucuronidase (GUSB). Studies to date have shown that methylation acts as an important mechanism for gene expression to suppress the metabolic enzymes of many chemotherapeutics. This study, which selected 99 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…In particular, CES2 is highly expressed in colon tumors, playing a key role in the metabolic activation of CPT-11 [ 9 , 10 ]. Recent results have shown that the expression of CES2 is related to tumor staging [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CES2 is highly expressed in colon tumors, playing a key role in the metabolic activation of CPT-11 [ 9 , 10 ]. Recent results have shown that the expression of CES2 is related to tumor staging [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…After being treated by DAC, the IC 50 value of the cells in each group except RK0 decreased; the IC 50 decline was not obvious in ls174T, DLD-1, HCT-116 and HCT-15 cells with positive UGT1A1 methylation [5] but significantly obvious in LoVo and HT-29 cells with negative UGT1A1 methylation [5], indicating that the methylation status of UGT1A1 could significantly affect the CPT-11 chemosensitivity, and the affecting degree varied with the type of colorectal cancer. While IC 50 value in the RK0 cells with low expression of UGT1A1 increased instead, indicating that this abnormal rise might be related to the process of demethylation ( Table 1).…”
Section: Influence Of Ugt1a1 Methylation On the Chemosensitivity Of Cmentioning
confidence: 82%
“…The author [5] has proved from the clinical perspective that aberrant methylation is the characteristic factor for regulating CPT-11 metabolic enzymes, and the aberrant methylation of UGT1A1 exists in tumor tissues. The role of its SN-39G for regulating enzyme enables it to have the potential to be the potential target of the process.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation may indirectly downregulate the activation of target genes by inhibiting the expression of TFs. In 2014, Xie et al also reported that in 99 patients with colorectal cancer, UGT1A1 promoter methylation could inhibit gene expression, thereby affecting the metabolic level of irinotecan (CPT-11) [ 50 ]. In summary, DNA methylation is expected to be a new target for drug resistance mechanisms.…”
Section: Epigenetics In Ugt1asmentioning
confidence: 99%